2011
DOI: 10.1143/jpsj.80.054002
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Quantum Gates, Composite Pulses, and Trotter–Suzuki Formulas

Abstract: We show that all geometric quantum gates (GQG's in short), which are quantum gates only with geometric phases, are robust against control field strength errors. As examples of this observation, we show (1) how robust composite rf-pulses in NMR are geometrically constructed and (2) a composite rf-pulse based on Trotter-Suzuki Formulas is a GQG.PACS numbers: 03.65. Vf, 82.56.Jn, Geometric phases have been attracting a lot of attention from the view point of the foundation of quantum mechanics and mathematical ph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 21 publications
2
19
0
Order By: Relevance
“…More precisely, we reveal that composite pulses robust against certain kinds of systematic errors are nothing but GQGs. This has been observed previously in one-qubit operations [36]. Now we elaborate and generalize this observation to two-qubit operations that are indispensable for a universal set of quantum gates in QIP.…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…More precisely, we reveal that composite pulses robust against certain kinds of systematic errors are nothing but GQGs. This has been observed previously in one-qubit operations [36]. Now we elaborate and generalize this observation to two-qubit operations that are indispensable for a universal set of quantum gates in QIP.…”
Section: Introductionsupporting
confidence: 75%
“…For example, Zanardi & Rasetti [24] proposed to use the Wilczek-Zee holonomy to implement unitary gates. It is also possible to implement unitary gates by using the Aharonov-Anandan phase [10,25,[36][37][38]. To see this, let {|j a } 1≤a≤n be the eigenvectors of a Hamiltonian H (l(0)) and suppose their dynamical evolution is cyclic, that is, When there is no degeneracy, the spectral decomposition of U (T ) is written as…”
Section: Geometric Quantum Gatesmentioning
confidence: 99%
See 1 more Smart Citation
“…, and V i denotes exp(−iθ i n i • σ/2) while V 0 is the identity matrix. In Ref [20], it is shown that if the above error robustness condition for PLE is satisfied, the operation by H 0 (t) in Eq. ( 15) is a geometric quantum gate [22][23][24] based on the concept of holonomy [25][26][27][28].…”
Section: A General Frameworkmentioning
confidence: 99%
“…For example, it was shown that any sequence robust against amplitude errors is a geometric quantum gate using AharonovAnandan phase [19,20]. Controlled-NOT and SWAP gates robust against coupling strength error were designed for Ising-type interactions [12].…”
Section: Introductionmentioning
confidence: 99%